Optimasi Praktikum Kimia: Peran Kontrol yang Efektif dalam Aktivitas Laboratorium - Rody Putra Sartika; Lukman Hadi; Hasan Argadinata; Arin Ika Puspitaningsih; Ghasa Faraasyatul ‘Alam (Postgraduate, University of Mataram, 2026)
This study examines the effectiveness of laboratory supervision in chemistry practicum activities in higher education. Effective supervision is essential to ensure student safety, structured learning processes, and optimal achievement of learning outcomes. A quantitative survey method was employed involving 88 undergraduate students from a Chemistry Education program who actively participated in chemistry laboratory practicums. Data were collected through structured online questionnaires using a dichotomous (Guttman) scale to capture the implementation of supervision practices. The questionnaire was validated through expert judgment and demonstrated acceptable reliability (Cronbach’s Alpha = 0.705). The data were analyzed using descriptive quantitative techniques to determine supervision effectiveness across five aspects based on predetermined effectiveness criteria. The results indicate that overall supervision effectiveness reached 81.69% (Good category). High effectiveness was found in practicum implementation (90.23%), laboratory assistant guidance (94.91%), equipment and materials (87.40%), and practicum guidelines (93.43%). However, lecturer guidance showed significantly lower effectiveness (42.50%, Poor category), indicating a critical gap in direct academic supervision. In conclusion, laboratory supervision has been effectively implemented in most aspects; however, strengthening lecturer involvement remains essential to improve learning quality and support instructional objectives in chemistry practicum activities.